A Structural Model of Job Burnout and Work-Family Conflict in Teachers, with the Mediating Role of Mental Health and Psychological Capital: A Gender Comparison - Niksirat , Fereshteh; Khademi Ashkzari, Molouk; Naghsh , Zahra (KMAN Counseling & Psychology Nexus, 2026)
The purpose of this research is to present a structural model of job burnout based on work-family conflict, mental health, and psychological capital, considering gender differences. The study population comprised sixth-grade teachers in Tehran, from which a sample of 400 individuals (223 female and 177 male) was selected using stratified sampling with equal allocation. Research instruments included the Maslach Burnout Inventory, the Carlson Work-Family Conflict Scale, the Goldberg and Hiller General Health Questionnaire, and the Luthans Psychological Capital Questionnaire. Data were analyzed using correlation matrix and structural equation modeling. All paths were significant at the p≤.01level, except for the path from work-family conflict to job burnout and the path from psychological capital to job burnout. Among these coefficients, mental health (β=0.82) had the largest effect on job burnout. Overall, 41% of the total variance in job burnout was explained by work-family conflict, mental health, and psychological capital. There was a difference between the job burnout models for women and men. Given the impact of mental health on job burnout and work-family conflict among teachers, it appears that providing counseling and specialized psychological workshops for teachers could be effective in reducing their levels of job burnout and work-family conflict.